Assessment of groundwater recharge and discharge processes in a loessical aquifer using a new computer code - Blarasin, Mónica Teresa (2015)
Rio Cuarto city and its rural surrounding area (400 km2) shows two major geological environments,formed by eolian and fluvial sediments. The main source of groundwater recharge is precipitation (P),with an annual mean rainfall of 799 mm; 75-80% concentrated in spring and summer. The aim of this paper is to show the water table behavior in the unconfined eolian aquifer (very fine sands and silts) taking into consideration recharge (R) and discharge (D) events. R was calculated using the watertable fluctuation method for a selected period (2002-2009) with a new computer code Likqo 1.0. Therecharge was estimated for both the hydrologic and calendar year. The first result was better according to the higher R-P regression coefficient obtained. It is important to highlight the recharge delay (daysor weeks) in relation to rain storms; a fact that can be linked to water table depth. The average R value for the entire series was 12% of P, the largest recharge occurring in the hydrologic periods 2002-2003 and 2007-2008 (14% P) and the lowest in 2004-2005 (10 % P). The ratio R/D for the total series was slightly negative, which means that aquifer discharge was dominant, coinciding with the lowest position of the water table.